biomedicalresearch 2019
DOI: 10.35841/biomedicalresearch.30-18-1162
|View full text |Cite
|
Sign up to set email alerts
|

The biocompatibility of resin composite materials on different stem cells.

Abstract: Objectives: Composite resins should undergo attentive tests to specify their biocompatibility before they have contact with the teeth, regardless of physico-mechanical properties. Hence, this study has been carried out to assess the knowledge of potential cellular responses and biological effects of composite resins on three different cells after two different exposure times. Methods: The composites Surefil SDR flow, Dentsply Caulk/ABD (SS), X-tra base flowable, Voco Cuxhaven Germany (XB), Venus Bulk Flow, Voc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…An increase in IL-1 levels also triggers the release of the anti-inflammatory cytokine IL-10 to restrain the increase of inflammation and tissue destruction [ 27 ]. Kamalak et al showed that after 24 hours of applying two different FCRs, the IL-6 and IL-8 levels secreted from the cells were balanced by increased IL-10 secretion [ 28 ]. Similarly, in this study, a significant IL-10 storm was detected in all groups at the end of the first day and increased up to 3-4 times from the baseline.…”
Section: Discussionmentioning
confidence: 99%
“…An increase in IL-1 levels also triggers the release of the anti-inflammatory cytokine IL-10 to restrain the increase of inflammation and tissue destruction [ 27 ]. Kamalak et al showed that after 24 hours of applying two different FCRs, the IL-6 and IL-8 levels secreted from the cells were balanced by increased IL-10 secretion [ 28 ]. Similarly, in this study, a significant IL-10 storm was detected in all groups at the end of the first day and increased up to 3-4 times from the baseline.…”
Section: Discussionmentioning
confidence: 99%
“…9 Furthermore, the LED light cure unit, which was used in this study to polymerize the resin cement, might also cause a negative effect because this light source may not completely polymerize the resin cement. 8 Subsequently, free monomer components, such as Bis-GMA, UDMA, TEGDMA camphorquinone, and HEMA, may be found. These free monomers have the potential to cause pulp injury and prevent a proper tissue healing process.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, self-adhesive resin cement is proposed to be utilized to seal vertical root fractures that will simplify the treatment. 8,9 Thus far, mineral trioxide aggregate (MTA) is a material of choice to seal the fracture gap since it has many beneficial properties, such as biocompatibility, closure density, mechanical strength, and the healing capacity of periradicular tissue. 10,11 Even though the clinical success of employing composite resin in intentional replantation showed more than 90% after two years following the treatment, 7 it is still necessary to evaluate its success histologically to evaluate the regeneration of periradicular tissue, particularly the epithelial thickness.…”
Section: Introductionmentioning
confidence: 99%